1993
DOI: 10.1002/bit.260420317
|View full text |Cite
|
Sign up to set email alerts
|

A model system for a fluorometric biosensor using permeabilized Zymomonas mobilis or enzymes with protein confined dinucleotides

Abstract: Using permeabilized Zymomonas mobilis or glucose-fructose oxidoreductase isolated from this microorganism a model system for biosensors with a protein confined NADP(H) cofactor for the determination of glucose, fructose, gluconolactone, and sorbitol was developed. Either permeabilized microorganisms containing the oxidoreductase or the pure enzyme were confined via membrane separation in a small measuring chamber, that was integrated into a flow injection analysis system (FIA). The measuring principle was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Substrates determined in this way include ethanol, lactate, pyruvate, phenylalanine, malate, glutamate, glycerol or aminobutyric acid, lactate dehydrogenase being an example of an enzyme. This methodology is of great use, has been the object of considerable research and new applications are still being found (10,11). However, NADH does not have suitable fluorescent properties for the application of EFMs to real samples; in the first place, its relatively low molar absortivity and quantum yield result in determinations with medium sensitivity; second, the spectral region where its fluorescent properties are displayed frequently gives rise to interference problems, especially when minimal sample treatment is desired.…”
Section: Classical Enzymatic±fluorometric Methodsmentioning
confidence: 99%
“…Substrates determined in this way include ethanol, lactate, pyruvate, phenylalanine, malate, glutamate, glycerol or aminobutyric acid, lactate dehydrogenase being an example of an enzyme. This methodology is of great use, has been the object of considerable research and new applications are still being found (10,11). However, NADH does not have suitable fluorescent properties for the application of EFMs to real samples; in the first place, its relatively low molar absortivity and quantum yield result in determinations with medium sensitivity; second, the spectral region where its fluorescent properties are displayed frequently gives rise to interference problems, especially when minimal sample treatment is desired.…”
Section: Classical Enzymatic±fluorometric Methodsmentioning
confidence: 99%